PENGARUH KOMPETENSI, KOMUNIKASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN PROPINSI SULAWESI TENGAH - Arafah, Moh. (Katalogis, 2015)
This research is almed to: 1) analyzing the effect of competence, communication and work culture simultaneously toward the employee performance, 2) analyzing the effect of competence partially towards the employee performance, 3) anlyzing the effect of communication partially towards the employee performance, 4) analyzing the effect of work culture partially towards the employee performance.This research is conducted as explanation research in explaining the relation between research variables which involves 58 Employees Of Education and Cultural Office Of Central Sulawesi which is taken using purposive sampling technique. Based on the result of the research using multiple regression analysis, concluded: 1) competence, communication and work culture simultaneously have a positive and significant effect toward the employee performance, 2) partially competence have a positive and significant effect towards the employee performance, 3) partially communication have a positive and significant effect towards the employee performance, 4) partially work culture have a positive and significant effect towards the employee performance